Pengaruh Jenis dan Konsentrasi Bahan Pengisi terhadap Karakteristik Komposit Bioplastik Pati Umbi Gadung-Karagenan - Suparwan, Komang Gede Irwan; Hartiati, Amna; Suhendra, Lutfi (JURNAL REKAYASA DAN MANAJEMEN AGROINDUSTRI, 2021)
This study aims to determine the effect of filler types and concentrations and their interactions on the characteristic bioplastic composites of gadung tuber starch-carrageenan, and to determine the types and concentrations of fillers that produce the best characteristic of the bioplastic composites of gadung tuber starch-carrageenan. This research used factorial randomized block design. The first factor is the type of filler consisting of 4 level that is ZnO, clay, CaCO 3 , nanocellulose. The second factor is the filler concentration consisting of 4 levels 0%, 5%, 10%, 15% (w/w). Each treatment is grouped into two time-based of making bioplastics, so there are 32 experimental units. The data obtained were analyzed of variant and test Tukey’s. Composite gadung tuber starch-carrageenan with nanocelluloce filler get the best a tensile strength value 19,33 MPa, elongation at break 10,47%, modulus young 185,06 MPa, biodegradability for 6 day, and contain asetil (C-O-C), alkenes (CH), alcohol, ethers, carboxylic acids, and esters (CO), alkene (C=C), alkyne (C?C), alcohol (OH). While the composite bioplastic of gadung tuber starch-carrageenan with ZnO filler material with a concentration of 15% the best swelling value 39.32% and the rate of water vapor transmission  0.56 g/hours.m 2 . Keywords :  bioplastic, gadung tuber starch-carrageenan, filler